1994
DOI: 10.1073/pnas.91.8.3393
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of immunoglobulins from amyotrophic lateral sclerosis patients on a hybrid motoneuron cell line.

Abstract: Patients with amyotrophic lateral sclerosis possess antibodies (ALS IgGs) that bind to L-type skeletal muscle voltage-gated calcium channels (VGCCs) MATERIALS AND METHODSCell Culture. Parental embryonic day 15 rat ventral spinal neuron preparation, mouse N18TG2 neuroblastoma culture, somatic cell fusion, and hybrid selection were performed as described (25,26). VSC 4.1 hybrid cells were maintained in logarithmic-phase growth on poly(L-ornithine)-precoated T-75 flasks (Coming) in Dulbecco's modified Eagle's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
74
0

Year Published

1994
1994
1999
1999

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(78 citation statements)
references
References 38 publications
2
74
0
Order By: Relevance
“…In this disease it has been reported that a large proportion of patients has circulating autoantibodies directed against the ␣ 1 subunit of VDCCs Kimura et al, 1994). It is thought that VDCCs in MN terminals at the NMJ may represent targets for these autoantibodies and may play a role in MN degeneration in ALS Smith et al, 1994;Mosier et al, 1995;Siklos et al, 1996).…”
mentioning
confidence: 99%
“…In this disease it has been reported that a large proportion of patients has circulating autoantibodies directed against the ␣ 1 subunit of VDCCs Kimura et al, 1994). It is thought that VDCCs in MN terminals at the NMJ may represent targets for these autoantibodies and may play a role in MN degeneration in ALS Smith et al, 1994;Mosier et al, 1995;Siklos et al, 1996).…”
mentioning
confidence: 99%
“…Differentiated I-VSC 4.1 cells expressing high levels of calbindin-D28K were significantly resistant to toxicity of ALS IgG (Fig. 6), which had been previously demonstrated to induce cell death of differentiated VSC 4.1 cells (7,15). After 48 h, the mean survival of differentiated I-VSC 4.1 cells incubated with ALS IgG was 98.1 + 13.1% compared to PBS-treated cultures.…”
Section: Resultsmentioning
confidence: 77%
“…In control experiments, the level of heavy-chain neurofilament protein mRNA as well as parvalbumin mRNA remained unchanged in I-VSC 4.1 cells. Similarly, the increase in neurofilament expression with cAMP differentiation reported in VSC 4.1 cells (15,24) (Fig. 4) godeoxynucleotide (E).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations